The right of the federal territories to independence: Kurdistan Region is a model - اىٍدرس اىدنخٔر ةراًْ٘ ٌدٍد صاىح (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The topic of our study is considered a very critical constitutional issue within the framework of the federal state. The study is an effort to shed light on the right of federal regions to independence as well as the issue of creating a sort of compromise between such a right and the principle of federalism sustainability in the light of the currently emerging developments and principles in the field of comparative constitutional law in addition to the provisions of the judgments passed by the institutions of Constitutional and Judicial review. The significance of this subject does not simply lie in the principle of its being a counter solution in the face of the federal authority's tyranny under the guise of the principle of federalism sustainability which allows the federal government to resort to a broad interpretation of the constitutional competencies and practice a kind of favoritism in favor of one region at the expense of another. It is rather an essential tool to maintain the vertical constitutional balance, as well as the need for conditional recognition of the right of federal regions to independence. To ensure that the study covers all matters and ideas relevant to its topic, I have divided it into three chapters with an introductory section for the objective of clarifying the concept of federal regions to independence and distinguishing it from the other confusing concepts among which are some common overlapping terms such as "Nullification" and the term of "Secession". In the first chapter, I have discussed the basis of the right of the federal regions to independence (the philosophical basis, the legal basis). While in the second chapter, I have covered the point of view of jurisprudence and the judiciary regarding the right of the federal regions to independence. As for the third chapter, it is rather a theoretical and practical topic that demonstrates the legality of the right of Kurdistan Region to independence. Finally, I have ended the study with a concluding section where I have stated the conclusions that I have reached in the course of the study and have also included some recommendations.